The Implementation of a Blooket-Assisted PBL Learning Model on Students’ Critical Thinking Skills in Economics at SMA N 2 Ungaran - Desika Husna; Ahmad Sehabuddin (Universitas Negeri Semarang, 2026)
Critical thinking ability is an essential competency that needs to be developed in economics learning, yet the dominance of conventional teaching methods remains a primary obstacle to its development. This study aimed to analyze the effectiveness of the Problem Based Learning (PBL) model assisted by Game Blooket in enhancing the critical thinking skills of Grade XI students at SMA Negeri 2 Ungaran on the topic of economic growth and development. This study employed a quantitative approach with a quasi-experimental Nonequivalent Control Group Design. The sample consisted of 36 students from Class XI 7 as the experimental group and 36 students from Class XI 8 as the control group, selected through purposive sampling. Research instruments included multiple-choice questions based on critical thinking competencies (C4, C5, C6). Data were analyzed using the Kolmogorov-Smirnov normality test, Levene's homogeneity test, Independent Sample T-Test, and N-Gain test. Results showed that: (1) the mean N-Gain of the experimental class was 0.717 (High category), higher than the control class at 0.641 (Medium category); (2) there was a significant difference between the learning outcomes of the experimental and control classes, evidenced by a sig. (2-tailed) value of 0.030 < 0.05 in the posttest Independent Sample T-Test. Therefore, the PBL model assisted by Game Blooket is proven effective in improving students' critical thinking skills in economics learning.